PHYSICAL EDUCATION AND THE PROEJA BASE DOCUMENT: INTEGRATION STRATEGY IN THE VOCATIONAL TRAINING OF YOUNG PEOPLE AND ADULTS - Lucas, Bianca Bissoli (Seven Editora, 2025)
One of the challenges of Professional Education for Youth and Adults is the construction of its own identity aimed at new educational spaces, including the construction of a school for young people and adults. To guide schools in the elaboration of their pedagogical project, based on the defined course, the Ministry of Education (MEC) in Brazil, constituted a working group responsible for the elaboration of a document entitled PROEJA Base Document (National Program for Professional Integration with Basic Education in the modality of Youth and Adults). The document states that the expansion of PROEJA is a strategy for integrating the training process, which would also result in a dialogue between educational contents, methodologies and practices. Therefore, this qualitative research of bibliographic nature aims to show the existence of the guiding institutional document for the PROEJA modality, and to indicate the need for adherence between the pedagogical practices of Physical Education of PROEJA, and the institutional proposals. We conclude that the contribution of the Physical Education curricular component to the educational project, far from prescriptive intentions, lies in thinking about the possible pedagogical interventions in the field of knowledge of this in the school in line with the current institutional project. In this sense, it is necessary that it be constituted as a school discipline, articulating its pedagogical practice with the other disciplines in the educational project of the school, and not as an isolated activity.DOI: https://doi.org/10.56238/sevened2025.018-026